E-government within Public Administration - Tsybulnyk, Nelli Yuriivna; Zadoia, Ivanna Ivanivna; Kurbatova, Iryna Serhiyivna; Mekh, Yuliia Volodimirivna (Jurnal Cita Hukum, 2020)
AbstractThe purpose of the article is to determine the nature, content, and characteristic features of e-government, as well as to analyze its impact on the implementation of public administration. While writing the article the following methods were used: logical, semantic, method of documentary analysis, and comparative legal. Specific features of modern models of e-government in the world have been analyzed; the expediency of introduction of the optimal model of the specified kind of government into the state system of Ukraine has been researched. The influence of modern high-tech means of e-government on the existing public administration systems in the world has been studied.  The author has suggested their definitions of «e-government», «public administration» and «e-governance». Authors have defined the perspective directions of the development of this sphere, which need to be developed to improve the general situation in the field of public administration. A comparative analysis was carried out with the leading countries in this field. Particular attention has been paid to the successful experience of developed foreign countries in organizing the process of e-government as a perspective form of public administration.Keywords: public administration, e-government, high technologies, administrative activity, modern means, effective strategies, legal regulation AbstrakArtikel ini bertujuan untuk mengetahui sifat, isi dan ciri khas e-government, serta menganalisis dampaknya terhadap penyelenggaraan administrasi publik. Saat menulis artikel metode berikut digunakan: logis, semantik, metode analisis dokumenter dan hukum komparatif. Ciri-ciri khusus model modern e-government di dunia telah dianalisis; kemanfaatan pengenalan model optimal dari jenis pemerintah tertentu ke dalam sistem negara Ukraina telah diteliti. Pengaruh sarana e-government berteknologi tinggi modern pada sistem administrasi publik yang ada di dunia telah dipelajari. Penulis telah menyarankan definisi «e-government», «administrasi publik» dan «e-governance» sendiri. Penulis telah menentukan arah perspektif perkembangan bidang ini, yang perlu dikembangkan untuk tujuan memperbaiki situasi umum di bidang administrasi publik. Analisis komparatif dilakukan dengan negara-negara terkemuka di bidang ini. Perhatian khusus telah diberikan pada pengalaman sukses negara-negara asing maju dalam menyelenggarakan proses e-government sebagai bentuk perspektif administrasi publik.Kata Kunci: Administrasi Publik, E-Government, Teknologi Tinggi, Kegiatan Administrasi, Sarana Modern, Strategi Efektif, Regulasi Hukum АннотацияЦелью статьи является определение сущности, содержания и характерных особенностей электронного управления, а также анализ его влияния на осуществление публичного администрирования. В работе анализируются особенности современных моделей электронного управления в мире, а также изучается целесообразность внедрения оптимальной модели указанного вида управления в государственную систему Украины. Рассмотрено влияние современных высокотехнологичных средств электронного управления на ныне существующие в мире системы публичного администрирования. Предлагается авторское определение понятия «электронное правительство», «публичное администрирование» и «электронное управление». Определяются перспективные направления развития этой сферы, которые нужно развивать для улучшения общей ситуации в области публичного администрирования. Обращается внимание на успешный опыт развитых зарубежных стран в организации процесса электронного управления как перспективной формы публичного администрирования.Ключевые слова: публичное администрирование, электронное управление, высокие технологии, управленческая деятельность, современные средства, эффективные стратегии, правовое регулирование, зарубежный опыт